Avaliando o impacto do Programa Banda Larga nas Escolas sobre a qualidade educacional - Alex Felipe Rodrigues Lima; Helena Karla Barbosa de Lima; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This study had the objective of evaluating the impact of the Broadband Program in Schools (PBLE) on the educational quality of schools. For this, two indicators were used: Basic Education Development Index (Ideb) and the average of the National High School Exam (Enem). Adopting differences-in-differences method (DiD) and Panel Data, with and without pairing, it was possible to demonstrate that: i) with data from Ideb referring to the initial years of elementar education, the impact of the program in schools was negative; and ii) in relation to the final years of elementary education, there were improvements in schools in the Southeast and Central West. In addition, the Enem data confirmed which schools in the Southeast region showed improvement in math test (MT), with a significant increase varying between 3% and 4% in performance, but worsened test scores for languages and codes (LC). For the Northeast region, the program had positive effects on the natural science test (NC), but negative on the MT test.
Keywords: D04; I28; C21; 330; educational quality; Broadband Program in Schools (PBLE); differences in differences method (DiD); evaluation of public policies